1992
DOI: 10.1152/ajpendo.1992.263.3.e507
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ovarian hormones on brain opioid binding sites in castrated female rats

Abstract: These experiments were performed to analyze whether treatments of ovariectomized female rats with ovarian steroid regimens able to induce either an increase (positive feedback effect) or a decrease (negative feedback effect) of serum levels of luteinizing hormone (LH) have some impact on the characteristics of mu-opioid binding sites in circumscribed areas of the brain. The increase of serum levels of LH elicited by a treatment with estradiol benzoate (EB) plus progesterone (P; positive feedback effect) was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
3

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 29 publications
1
21
3
Order By: Relevance
“…Since some effects of androgens are medi- ated by their conversion to estradiol [20,45], further work will be required to determine their actual pain modulation by using aromatase inhibitors to prevent the conversion of testosterone to estradiol. Evidence has shown that estradiol administration to OVX rats increases μ-opioid receptor protein in the hypothalamus [46][47][48] and enkephalin mRNA expression [49], indicating that estrogen can induce an increase in endogenous antinociception and thus reduce pain sensitivity. The P2X 3 receptor subtype has been found to be involved in peripheral pain signal transduction [26,[50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Since some effects of androgens are medi- ated by their conversion to estradiol [20,45], further work will be required to determine their actual pain modulation by using aromatase inhibitors to prevent the conversion of testosterone to estradiol. Evidence has shown that estradiol administration to OVX rats increases μ-opioid receptor protein in the hypothalamus [46][47][48] and enkephalin mRNA expression [49], indicating that estrogen can induce an increase in endogenous antinociception and thus reduce pain sensitivity. The P2X 3 receptor subtype has been found to be involved in peripheral pain signal transduction [26,[50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone and Opioid Interaction possible target of sex steroids. Recently, Dondi et al [21] demonstrated that estradiol treat ment increased the number of p-binding sites in the hippocampus and in the thalamus but not in the hypothalamus. After acute estradiol plus progesterone treatment, there was a significant increase in hypothalamic P-endorphin levels.…”
Section: Discussionmentioning
confidence: 99%
“…LIGAND and DESIGN computer pro grams were used, respectively, to analyze the ligand-binding data and to optimize the experimental protocols. A detailed description of these programs can be found in previous reports [25,26]. The LIGAND program was used to analyze simultaneously the five homologous inhibition curves arising from each experimental group, in order to estimate the binding parameters (Bmax and Kd) represen tative for each group.…”
Section: Statistical a Nalysismentioning
confidence: 99%